Neuroimaging Pearls from the MDS Congress Video Challenge. Part 1: Genetic Disorders. Issue 3 (3rd February 2022) - Olszewska, Diana A.; Rawal, Sapna; Fearon, Conor; Alcaide‐Leon, Paula; Stell, Rick; Paramanandan, Vijayashankar; Lynch, Tim; Jawad, Tania; Vittal, Padmaja; Barton, Brandon; Miyajima, Hiroaki; Kono, Satoshi; et al.
Abstract: We selected several "imaging pearls" presented during the Movement Disorder Society (MDS) Video Challenge for this review. While the event, as implicated by its name, was video‐centered, we would like to emphasize the important role of imaging in making the correct diagnosis. We divided this anthology into two parts: genetic and acquired disorders. Genetic cases described herein were organized by the inheritance pattern and the focus was put on the imaging findings and differential diagnoses. Despite the overlapping phenotypes, certain described disorders have pathognomonic MRI brain findings that would provide either the "spot" diagnosis or result in further investigations leading to the diagnosis. Despite this, the diagnosis is often challenging with a broad differential diagnosis, and hallmark findings may be present for only a limited time.